BRYOPHYTE PHYLOGENY AND LINEAGES: A REVIEW PAPER - Losenara, Jleian Mard M (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Plants play a crucial role in supporting the existenceof life. Plants are regulators of ecosystem processes; establish complex relationships with other organisms; and possess interesting biodiversification. Regarded as the ancestors of plants, most bryophytes lack extensive tissue organization and show substantial variety in shape and ecology. The bryophytes, or nonvascular seedless plants, are divided into three groups: mosses (Bryophyta), hornworts (Anthocerotophyta) , and liverworts (Marchantiophyta) . Anchored on extant works and relevant literature, this review paper intended to trace the phylogeny of bryophytes and the within relationships of its lineages. Understanding these patterns is vital in unlocking plant evolution and future direction. The review paper sought to identify the position of bryophytes in plant evolution. Though traditionally liverworts were basal of the bryophytes, recent studies and molecular analysis show hornworts to be the first of the bryophytes. Mosses form a link between bryophytes and tracheophytes, the ancestors of land plants.